A woman's disease : the history of cervical cancer - Lowy, Ilana, 1948- (Oxford University Press, 2011)
Cervical cancer is an emotive disease with multiple connotations. It has stood for the horror of cancer, the curse of femininity, the hope of cutting-edge medical technologies and the promise of screening for malignant tumours. For a long time, this disease was identified with the most dreaded aspects of malignancies: prolonged invalidity and chronic pain, but also physical degradation, shame and social isolation. Cervical cancer displayed in parallel the dangers of being a woman. In the 20th century, innovations initially developed to control cervical cancer - radiotherapy and radium therapy.